The Lasting Effect of Sex Ratio Imbalance on Marriage and Family: Evidence from World War II in Russia - Elizabeth Brainerd (Institute for the Study of Labor (IZA), 2016)
How does a shock to sex ratios affect marriage markets and fertility? I use the drastic change in sex ratios caused by World War II to identify the effects of unbalanced sex ratios on Russian women. Using unique data from the Soviet archives, the results indicate that male scarcity led to lower rates of marriage and fertility, higher nonmarital births and reduced bargaining power within marriage for women most affected by war deaths. The impact of sex ratio imbalance on marriage and family persisted for years after the war's end, and was likely magnified by policies that promoted nonmarital births and discouraged divorce.
Keywords: J12; J16; N34; P23; 330; sex ratios; marriage; family; fertility; divorce law